2020
DOI: 10.1111/his.14050
|View full text |Cite|
|
Sign up to set email alerts
|

Immunopathology of Kikuchi–Fujimoto disease: A reappraisal using novel immunohistochemistry markers

Abstract: Aims Kikuchi–Fujimoto disease (KFD) is a self‐limited disease characterised by destruction of the lymph node parenchyma. Few studies have assessed the immunohistological features of KFD, and most employed limited antibody panels that lacked many of the novel immunohistochemistry markers currently available. Methods and results We used immunohistochemistry to reappraise the microanatomical distribution of plasmacytoid dendritic cells (pDCs), follicular helper T cells and cytotoxic T cells, B cells, follicular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
14
0
2
Order By: Relevance
“…Microscopic examination can also demonstrate paracortical foci of histiocytic infiltrate, with characteristic absence of neutrophils and eosinophils with few or no plasma cells [19]. The immunohistologic landscape of KFD is complex and characterized by increased numbers of plasmacytoid dendritic cells that frequently cluster around apoptotic/necrotic foci, increased cytotoxic T-cells, and substantial distortion of follicular dendritic cell mesh works [25]. However, in the case reported, histological examination of the cervical lymph node revealed necrotizing lymphadenopathy with severe plasmacytosis.…”
Section: Sporadic Cases Of Kikuchi's Disease Have Been Reported Inmentioning
confidence: 88%
“…Microscopic examination can also demonstrate paracortical foci of histiocytic infiltrate, with characteristic absence of neutrophils and eosinophils with few or no plasma cells [19]. The immunohistologic landscape of KFD is complex and characterized by increased numbers of plasmacytoid dendritic cells that frequently cluster around apoptotic/necrotic foci, increased cytotoxic T-cells, and substantial distortion of follicular dendritic cell mesh works [25]. However, in the case reported, histological examination of the cervical lymph node revealed necrotizing lymphadenopathy with severe plasmacytosis.…”
Section: Sporadic Cases Of Kikuchi's Disease Have Been Reported Inmentioning
confidence: 88%
“…Additionally, we found the increase in pDCs to be patchy and proportionally lower than the increased pDCs typical of KFD, findings supported by prior studies. [26][27][28][29][30][31] For example, Rollins-Raval et al 28 reported fewer pDCs in viral infections (including CMV, HIV, Hepatitis C and a case of chronic HIV and EBV) compared to KFD and other causes of granulomatous inflammation. pDCs are known to migrate from the bone marrow to T-cell rich areas of lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The histiocytes have crescent-shaped nuclei and phagocytosed debris, which differentiate it from other lymphadenopathies such as tubercular lymphadenitis or lymphoma [ 7 , 9 , 11 ]. Some previous research proposed that cytotoxic T cells are important in the pathogenesis of, and on IHC, CD8-positive T cells were predominant in the lymphoid follicles [ 17 ]. Our IHC also confirmed a dominance of CD8-positive T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%